Word square english learning media design assisted by the Canva application - Sugianto, Sugianto; Darmayanti, Rani; Arian Sah, Retno Wahyu; Usmiyatun (Bulletin of Educational Management and Innovation, 2023)
Students in learning English "difficult, vocabulary, boring, do not understand". This is due to the lack of English vocabulary that students have regarding pronunciation and pronunciation. Lack of interesting and not boring learning media to help students expand their vocabulary when learning English. The purpose of this research is to make a Word Square media product supported by the Canva application in learning English that is valid as an experiment to expand the vocabulary of seventh grade junior high school students. The method used is 4D model development. This research is only limited to development, namely the third stage only. The results of the verification score were 4.47 from both media and 4.81 from both material expert verifiers in the very valid category. From the evaluation results, it was found that the Word Square media supported by the Canva application is suitable for learning English.